UJI AKTIVITAS ANTIBAKTERI EKSTRAK PROTEIN DAUN MIRABILIS JALAPA L. TERHADAP BAKTERI STAPHYLOCOCCUS EPIDERMIDIS DAN PROPIONIBACTERIUM ACNES - , ARSA WAHYU NUGRAHANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
RIPs Mirabilis jalapa L. has been known to have many activities such as cleavage supercoiled double-stranded DNA, RNA N-glycosidase activity, anticancer activity, anti-inflammatory and inhibition of the growth of nodules on animals. Pathogenesis of acne is caused by clogged pores in the skin and sebum accumulation caused by bacteria. Previous studies have reported that RIPs ME1 and ME2 from Mirabilis expansa have the antibacterial and antifungal activity. This study is therefore aimed to determine the antibacterial activity of Mirabilis jalapaâs L. RIPs against bacteria Staphylococcus epidermidis and Propionibacterium acnes bacterium that are involved in acne pathogenesis will be also studied in this research mechanism of inhibition of bacterial growth and bacterial cell death. Protein from Mirabilis jalapa L. leaves was precipitated using acetone and then the resulted protein was tested on the activity of supercoiled DNA double strand cleavage. Antibacterial activity was tested using diffusion method while the determination of MIC and MBC was carried out by dilution method. Process of bacterial inhibition and cell death were analyzed by leakage test cell. Result of this study showed that RIPs contained in protein extracts Mirabilis jalapa L. have activity of supercoiled DNA double strand cleavage. The protein extracts have antibacterial activity on Staphylococcus epidermidis with MIC value of 10 mg / mL and is included as bacteriostatic (start from 250 Âµg of loading protein extract). The process of cell growth inhibition of Staphylococcus epidermidis presumably through the mechanism of cell wall damage due to the presence of nucleic acids, proteins, ions K+ and Ca2+ on the outside of the bacterial cell. Mirabilis jalapa L. extract protein does not provide the antibacterial activity on Propionibacterium acnes.